Genome-wide characterization and functional identification of MYB genes in Malus sieversii infected by Valsa mali - Ding, Yu; Yang, Qihang; Waheed, Abdul; Zhao, Mingqi; Liu, Xiaojie; Kahar, Gulnaz; Haxim, Yakupjan; Wen, Xuejing; Zhang, Daoyuan (Frontiers in Plant Science, 2023)
Among the most important transcription factors in plants, the v-myb avian myeloblastosis viral oncogene homolog (MYB) regulates the expression network of response genes under stresses such as fungal infection. In China, the canker disease Valsa mali threatens the survival of Malus sieversii, an ancestor of cultivated apples. Using the M. sieversii genome, we identified 457 MsMYB and 128 R2R3-MsMYB genes that were randomly distributed across 17 chromosomes. Based on protein sequence and structure, the R2R3-MsMYB genes were phylogenetically divided into 29 categories, and 26 conserved motifs were identified. We further predicted cis-elements in the 2000-kb promoter region of R2R3-MsMYBs based on the genome. Transcriptome analysis of M. sieversii under V. mali infection showed that 27 R2R3-MsMYBs were significantly differentially expressed, indicating their key role in the response to V. mali infection. Using transient transformation, MsMYB14, MsMYB24, MsMYB39, MsMYB78, and MsMYB108, which were strongly induced by V. mali infection, were functionally identified. Among the five MsMYBs, MsMYB14 and MsMYB78 were both important in enhancing resistance to diseases, whereas MsMYB24 inhibited resistance. Based on the results of this study, we gained a better understanding of the MsMYB transcription factor family and laid the foundation for a future research program on disease prevention strategies in M. sieversii.